Hepatectomy after bile duct injury: a systematic review. Issue 2 (February 2022) - Furtado, Ruelan; Yoshino, Osamu; Muralidharan, Vijayaragavan; Perini, Marcos V.; Wigmore, Stephen J.
Abstract: Background: Bile duct injury (BDI) after cholecystectomy can lead to recurrent cholangitis, even after biliary reconstruction. This necessitates hepatectomy in a minority of patients. A systematic review was conducted, summarizing the pattern of biliary injury sustained in this group and their outcomes after hepatectomy. Methods: A literature search included the MEDLINE, EMBASE, PubMed and Cochrane libraries. Retrospective cohort studies describing outcomes for hepatectomy after BDI, and the nature of the antecedent BDI, published between 1999 and 2019, were selected. Results: Eight articles described a cohort of 2110 patients with BDI. Of these, 84 underwent hepatectomy. Complex vasculo-biliary injuries had been sustained in most cases. The mean time to hepatectomy was between 26 and 224 months after BDI. A right hepatectomy was performed in 67–89% of cases. Post hepatectomy, intra-abdominal infection (range 0–50%) and bile leaks (range 0–45%) occurred variably. Mortality occurred in three series. Nineteen percent of patients (16 of 84) developed recurrent symptoms at follow up. Conclusion: Hepatectomy after bile duct injury is an uncommon procedure and represents a salvage strategy when vasculo-biliary injury happens. Liver resection leads to resolution of symptoms in the majority of the cases however postoperative bile leaks and intra-abdominal infection are common.